2008
DOI: 10.1016/j.cub.2007.12.058
|View full text |Cite
|
Sign up to set email alerts
|

RACK1 Inhibits TRPM6 Activity via Phosphorylation of the Fused α-Kinase Domain

Abstract: We propose a unique mode of TRPM6 regulation in which the Mg(2+) influx is controlled by RACK1 through its interaction with the alpha-kinase and the phosphorylation state of the threonine(1851) residue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 36 publications
2
62
0
Order By: Relevance
“…Several experiments were conducted to explain the molecular mechanism behind the insensitivity of the TRPM6 variants to insulin. The role of the kinase activity present in TRPM6 was excluded by showing that the phosphotransferase-deficient mutant TRPM6(K 1804 R) was still stimulated by insulin (17). Cross-species sequence alignment of TRPM6 suggested the presence of two potential phosphorylation sites, TRPM6(T 1391 ) and TRPM6 (S 1583 ), in the vicinity of the SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Several experiments were conducted to explain the molecular mechanism behind the insensitivity of the TRPM6 variants to insulin. The role of the kinase activity present in TRPM6 was excluded by showing that the phosphotransferase-deficient mutant TRPM6(K 1804 R) was still stimulated by insulin (17). Cross-species sequence alignment of TRPM6 suggested the presence of two potential phosphorylation sites, TRPM6(T 1391 ) and TRPM6 (S 1583 ), in the vicinity of the SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…The lower abundant product bands of different sizes might be due to binding of so far unknown proteins to the bigger truncation mutants or degradation products. To explore the REA binding site in the TRPM6 ␣-kinase domain, the tertiary structure of this domain was modeled by SWISS-MODEL based on the homology between TRPM6 and TRPM7 ␣-kinase domains (15,31). Because of the significant homology between the TRPM6 and TRPM7 ␣-kinase domains (84%), these two domains share a well-conserved secondary structure.…”
Section: Rea Associates With Trpm6-tomentioning
confidence: 99%
“…Remarkably, TRPM6 contains a C-terminal ␣-kinase domain, of which the regulatory role on channel activity remains elusive (12)(13)(14). It has been shown that RACK1 can interact with this domain and inhibit channel activity in a phosphorylation-dependent manner (15). A recent study demonstrated that the ATP binding motif in the ␣-kinase domain is required for modulation of TRPM6 channel activity by intracellular ATP (16).…”
mentioning
confidence: 99%
“…The C terminus of the TRPM subfamily harbors a coiled-coil region, which is involved in channel tetramerization and is critical for channel activation (7, 8, 14 -16). The members TRPM6 and TRPM7 contain a unique ␣-kinase domain at the far end of the C terminus, which regulates channel activity by a variety of molecular mechanisms (17,18).From the subfamily of TRPV channels, TRPV1-4 play a role in sensory signaling, whereas the Ca 2ϩ -selective and highly homologous TRPV5 and TRPV6 channels are crucial players in Ca 2ϩ homeostasis. Like the other members of this TRPV subfamily the C terminus of TRPV5 is relatively short as compared with the N terminus.…”
mentioning
confidence: 99%
“…The C terminus of the TRPM subfamily harbors a coiled-coil region, which is involved in channel tetramerization and is critical for channel activation (7, 8, 14 -16). The members TRPM6 and TRPM7 contain a unique ␣-kinase domain at the far end of the C terminus, which regulates channel activity by a variety of molecular mechanisms (17,18).…”
mentioning
confidence: 99%